Disseminated dermatophytosis and acquired immunodeficiency syndrome:literature review and presentation of clinical experience - Knauf Lopes, Vanessa; Herrera Garzon, Ivan Mauricio; Suazo Encarnacion, Paloma Marianni; José Martins, Carlos; Barbosa Lima, Ricardo; Neves Motta, Rogerio; Ferry, Fernando Raphael de Almeida (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Dermatophytosis are very common fungal infections caused by the fungal species Microsporum, Epidermophyton or Trichophyton, which mostly affect the skin, the interdigital region, groin and scalp. Although they do not cause serious diseases, in patients with the human immunodeficiency virus the infection manifests itself and evolves exuberantly, usually with extensive and disseminated lesions. Objective: To review the literature on dermatophytosis in people living with human immunodeficiency virus and to present the experience in clinical care in a patient living with human immunodeficiency virus with extensive and disseminated dermatophytosis. Methods: A literature review on the topic was carried out in the PubMed/National Library of Medicine – USA databases, using the keywords dermatophytosis, or dermatophytosis associated with the words AIDS, human immunodeficiency virus or immunodeficiency, from 1988–2022. The clinical experience showed a patient living with human immunodeficiency virus developing AIDS and presenting with disseminated skin lesions. Samples of the lesion were collected by scraping, which were submitted to culture and there was growth of fungi of the Trichophyton sp genus. A biopsy of the lesion was also performed using the Grocott-Gomori's Methenamine Silver stain. Results: We found 1,014 articles, of which only 34 presented a direct correlation with our paper, and were used to discuss the main themes narrated in this article. We present clinical experience in the management of a patient with human immunodeficiency virus/AIDS and low adherence to antiretroviral treatment, showing extensive and disseminated erythematous-squamous lesions with a clinical diagnosis of tinea corporis, manifesting with a clinical picture usually not found in immunocompetent patients. The diagnosis was confirmed by laboratory tests with isolation of the Trichophyton sp fungus. The patient was treated with oral fluconazole, with complete remission of the clinical picture after two months. She was also thoroughly encouraged to use the prescribed antiretroviral medication correctly. Conclusion: Dermatophytosis in patients living with human immunodeficiency virus can present extensive and disseminated forms. The antifungal treatment is quite effective, with remission of the condition. Antiretroviral therapy is an important adjuvant for better recovery of the sickness.